EXPLORATIVE STUDY: BRAND LOVE AND E-WOM AND THEIRINFLUENCE ON CUSTOMER ENGAGEMENT IN ELFORMULA PRODUCTS ON SHOPEE - Della Wahyuni Puspita Sari; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
The purpose of the study was to determine brand love and e-WOM and their effect on customer engagement on Elformula products in Shopee and to find out which factor is the most dominant in influencing customer engagement. This research uses quantitative methods on 65 respondents. The population used in this study was customer engagement for Elformula products at Shopee and sampling in this study using non-probability sampling techniques. Based on the results of multiple linear regression, the regression equation Y = 16.916 + 0.292 (X1) + 0.456 (X2) is obtained. The results concluded that brand love and e-WOM have a positive and significant effect both partially and simultaneously on customer engagement on Elformula products in Shopee.